------------------------------------------------------------------------
-- The two definitions of substitutions are isomorphic (assuming
-- extensionality)
------------------------------------------------------------------------

open import Universe

module deBruijn.Substitution.Isomorphic
  {i u e} {Uni : Indexed-universe i u e} where

import deBruijn.Context; open deBruijn.Context Uni
open import deBruijn.Substitution.Data.Basics as D using (ε; _▻_; [_])
open import deBruijn.Substitution.Function.Basics as F
  using (ε⇨; _▻⇨_) renaming (_▻⇨[_]_ to _▻⇨[_]F_)
open import Function using (_$_)
open import Function.Inverse using (Inverse)
open import Level using (_⊔_)
import Relation.Binary.PropositionalEquality as P

open P.≡-Reasoning

isomorphic :
   {t} {T : Term-like t} 
  P.Extensionality (i  u  e) (i  u  e  t) 
   {Γ Δ} {ρ̂ : Γ ⇨̂ Δ} 
  Inverse ([ Var  T ]-setoid ρ̂) (P.setoid $ D.Sub T ρ̂)
isomorphic {T = T} ext = record
  { to         = record { _⟨$⟩_ = to _
                        ; cong  = λ ρ₁≅ρ₂  D.≅-⇨-⇒-≡ $ to-cong ρ₁≅ρ₂
                        }
  ; from       = P.→-to-⟶ from
  ; inverse-of = record
    { left-inverse-of  = from∘to _
    ; right-inverse-of = λ ρ  D.≅-⇨-⇒-≡ $ to∘from ρ
    }
  }
  where
  to :  Γ {Δ} {ρ̂ : Γ ⇨̂ Δ}  F.Sub T ρ̂  D.Sub T ρ̂
  to ε               ρ = ε
  to (Γ  σ) {ρ̂ = ρ̂} ρ =
    P.subst  v  D.Sub T (t̂ail ρ̂ ▻̂ v))
            (≅-Value-⇒-≡ $ P.sym $ F.head-lemma ρ)
            (to Γ (F.tail ρ)  F.head ρ)

  from :  {Γ Δ} {ρ̂ : Γ ⇨̂ Δ}  D.Sub T ρ̂  F.Sub T ρ̂
  from ε       = ε⇨
  from (ρ  t) = from ρ ▻⇨ t

  to-▻ :  {Γ Δ σ} {ρ̂ : Γ  σ ⇨̂ Δ} (ρ : F.Sub T ρ̂) 
         D._≅-⇨_ (to (Γ  σ) ρ) (to Γ (F.tail ρ)  F.head ρ)
  to-▻ {ρ̂ = ρ̂} ρ =
    D.drop-subst-Sub  v  t̂ail ρ̂ ▻̂ v)
                     (≅-Value-⇒-≡ $ P.sym $ F.head-lemma ρ)

  abstract

    to-cong :  {Γ₁ Δ₁} {ρ̂₁ : Γ₁ ⇨̂ Δ₁} {ρ₁ : F.Sub T ρ̂₁}
                {Γ₂ Δ₂} {ρ̂₂ : Γ₂ ⇨̂ Δ₂} {ρ₂ : F.Sub T ρ̂₂} 
              F._≅-⇨_ ρ₁ ρ₂  D._≅-⇨_ (to Γ₁ ρ₁) (to Γ₂ ρ₂)
    to-cong {Γ₁ = ε}     {ρ₁ = _ , _} {ρ₂ = ._ , _}     [ P.refl ] = P.refl
    to-cong {Γ₁ = Γ  σ} {ρ₁ = ρ₁}    {ρ₂ = ._ , corr₂} [ P.refl ] =
      let ρ₂ = [_⟶_].function ρ₁ , corr₂ in begin
       [ to (Γ  σ) ρ₁                ]  ≡⟨ to-▻ ρ₁ 
       [ to Γ (F.tail ρ₁)  F.head ρ₁ ]  ≡⟨ D.▻⇨-cong P.refl (to-cong [ P.refl ]) P.refl 
       [ to Γ (F.tail ρ₂)  F.head ρ₂ ]  ≡⟨ P.sym $ to-▻ ρ₂ 
       [ to (Γ  σ) ρ₂                ]  

  from-cong :  {Γ₁ Δ₁} {ρ̂₁ : Γ₁ ⇨̂ Δ₁} {ρ₁ : D.Sub T ρ̂₁}
                {Γ₂ Δ₂} {ρ̂₂ : Γ₂ ⇨̂ Δ₂} {ρ₂ : D.Sub T ρ̂₂} 
              D._≅-⇨_ ρ₁ ρ₂  F._≅-⇨_ (from ρ₁) (from ρ₂)
  from-cong P.refl = [ P.refl ]

  abstract

    from∘to :  Γ {Δ} {ρ̂ : Γ ⇨̂ Δ} (ρ : F.Sub T ρ̂) 
              F._≅-⇨_ (from (to Γ ρ)) ρ
    from∘to ε ρ =
      ε⇨  ≅-⟶⟨ sym-⟶ $ F.ηε ext ρ 
      ρ   ∎-⟶
    from∘to (Γ  σ) {ρ̂ = ρ̂} ρ =
      from (to (Γ  σ) ρ)                 ≅-⟶⟨ from-cong $ to-▻ ρ 
      from (to Γ (F.tail ρ)  F.head ρ)   ≅-⟶⟨ _ ∎-⟶ 
      from (to Γ (F.tail ρ)) ▻⇨ F.head ρ  ≅-⟶⟨ F.▻⇨-cong P.refl (from∘to Γ (F.tail ρ)) P.refl 
      F.tail ρ ▻⇨ F.head ρ                ≅-⟶⟨ sym-⟶ $ F.η▻ ext ρ 
      ρ                                   ∎-⟶

    to∘from :  {Γ Δ} {ρ̂ : Γ ⇨̂ Δ} (ρ : D.Sub T ρ̂) 
              D._≅-⇨_ (to Γ (from ρ)) ρ
    to∘from ε                 = P.refl
    to∘from (_▻_ {σ = σ} ρ t) = begin
      [ to (_  _) (from ρ ▻⇨ t)            ]  ≡⟨ to-▻ (from ρ ▻⇨ t) 
      [ to _ (F.tail (from ρ ▻⇨[ σ ]F t)) 
        F.head (from ρ ▻⇨[ σ ]F t)          ]  ≡⟨ D.▻⇨-cong P.refl (to-cong [ P.refl ]) P.refl 
      [ to _ (from ρ)  t                   ]  ≡⟨ D.▻⇨-cong P.refl (to∘from ρ) P.refl 
      [ ρ  t                               ]